On the implications of knowledge bases for regional innovation policies in Germany - Hassink, Robert; Plum, Oliver; Rickmers, Arne (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2014)
Regional innovation policies have been criticised for being too standardised, one-size-fits-all and place-neutral in character. Embedded in these debates, this paper has two aims: first, to analyse whether industries with different knowledge bases in regions in Germany have different needs for regional innovation policies, and secondly, to investigate whether knowledge bases can contribute to the fine-tuning of regional innovation policies in particular and to a modern, tailor-made, place-based regional innovation policy in general. It concludes that although needs differ due to differences in knowledge bases, those bases are useful only to a limited extent in fine-tuning regional innovation policies.
Keywords: regional innovation policy; place-based approach; knowledge bases; fine-tuning